RBOH-mediated ROS production facilitates lateral root emergence in Arabidopsis - Orman-Ligeza, Beata; Parizot, Boris; de Rycke, Riet; Fernandez, Ana; Himschoot, Ellie; Van Breusegem, Frank; Bennett, Malcolm J.; Périlleux, Claire; Beeckman, Tom; Draye, Xavier (Company of Biologists, 2016)
Lateral root (LR) emergence represents a highly coordinated process in which the plant hormone auxin plays a central role. Reactive oxygen species (ROS) have been proposed to function as important signals during auxin-regulated LR formation, however their mode of action is poorly understood. Here, we report that Arabidopsis roots exposed to ROS show increased LR numbers due to the activation of LR pre-branch sites and LR primordia (LRP). Strikingly, ROS treatment can also restore LR formation in pCASP1:shy2-2 and aux1 lax3 mutant lines in which auxin-mediated cell wall accommodation and remodeling in cells overlying the sites of LR formation is disrupted. Specifically, ROS are deposited in the apoplast of these cells during LR emergence, following a spatio-temporal pattern that overlaps the combined expression domains of extracellular ROS donors of the RESPIRATORY BURST OXIDASE HOMOLOGS (RBOH). We also show that disrupting (or enhancing) expression of RBOH in LRP and/or overlying root tissues decelerates (or accelerates) the development and emergence of LRs. We conclude that RBOH-mediated ROS production facilitates LR outgrowth by promoting cell wall remodeling of overlying parental tissues.